Community Service to Develop Businesses in the 'Tuah Negri' Enterprise to Enhance National Competitiveness in Collaboration with the Ministry of Cooperatives and SMEs - Hidayat, Danny (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2023)
The community service project at